Compensation, Career Development, and Employee Performance at PT Pos Indonesia (Persero) Bandung City - et. al., R. Achmad Drajat Aji, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine how the description of compensation, career development, and employee performance at Pos Indonesia (Persero) Bandung City. In addition, to find out how much influence the provision of compensation and career development on employee performance at Pos Indonesia (Persero) Bandung City. The research method used in this research is descriptive and verification methods. The population in this study were 132 employees of PT Pos Indonesia (Persero) Bandung. The sampling technique used in this study is probability sampling with simple random sampling technique, and using the Slovin formula so that the total sample size is 100 people. The analytical method used in this study is multiple linear regression analysis. The results showed that the compensation, career development, and employee performance at PT Pos Indonesia (Persero) Bandung were included in the quite good category. In addition, the results of the study indicate that compensation and career development have an effect on employee performance. The magnitude of the influence of career development in contributing to the influence of employee performance is 60.7%.